Influence of social networks in healthcare on preparation for selection procedures of health professions education: a Dutch interview study. Issue 10 (31st October 2022) - Mulder, Lianne; Wouters, Anouk; Fikrat-Wevers, Suzanne; Koster, Andries S; Ravesloot, Jan Hindrik; Croiset, Gerda; Kusurkar, Rashmi A
Abstract : Objectives: Health professions education (HPE) students are often not representative of the populations they will serve. The underrepresentation of non-traditional students is problematic because diversity is essential for promoting excellence in health education and care. This study aimed to understand the perceptions of traditional and non-traditional students regarding facilitators and barriers in preparing for HPE selection procedures, and to determine the role of social networks in their decision-making and preparations to apply. Methods: A qualitative study was conducted with 26 Dutch youth who were interested in university-level HPE programmes. Semistructured interviews and sociograms were analysed using thematic analysis, adopting a constructivist approach. Results: Twenty-six high school students participated, with traditional and non-traditional backgrounds, with and without social networks in healthcare and higher education. Two themes were constructed. First, four high-impact facilitators helped to overcome barriers to apply and in preparation for selection: access to a social network connection working or studying in healthcare, to correct information, to healthcare experience and to a social network connection in higher education. Lack of information was the main barrier while access to social network connections in healthcare was the main facilitator to overcome this barrier. However, this access was unevenly distributed. Second, access alone is not enough: the need for agency to make use of available facilitators is also essential. Conclusions: The themes are discussed using intersectionality. Traditional students with access to facilitators develop their self-efficacy and agency within social structures that privilege them, whereas non-traditional students must develop those skills without such structures. Our findings provide recommendations for the ways in which universities can remove barriers that cause unequal opportunities to prepare for the selection of HPE programmes. Along with equitable admissions, these recommendations can help to achieve a more representative student population and subsequently a better quality of health education and care.